Remediation of bromate contaminated groundwater - Butler, R. M. (Cranfield University, 2005)
Bromate (BrO3") is a by-product formed at concentrations of 0.4 - 60 µg L'' during potable water ozonation. Following World Health Organisation designation as a `possible human' carcinogen, a 10 pg L" drinking water limit was introduced in England and Wales. Discovery of bromate contamination within a UK aquifer highlighted a knowledge gap, addressed by this project, relating to environmental behaviour and groundwater remediation. Following selection of an anion analysis strategy utilising Ion Chromatography (IC), bromate behaviour in wastewater was investigated as contaminated groundwater ingress to treatment processes was deemed possible. Respiration of wastewater biomass was unaffected by spiking of < 200 mg Ul bromate or bromide, with pilot-scale process dosing trials (S 100 mg L') using a Membrane Bioreactor (MBR) also exhibiting little negative effect following biomass acclimation. Bromate reduction to bromide was observed in a continuous-flow suspended growth chemostat bioreactor at retention times of 20 - 80 hours. A biological mechanism was confirmed in this system, with reduction mediated by indigenous groundwater bacteria following glucose addition. Bromate reduction rates were initially low (5 27.8 pg U' hr 1), but acclimation increased rates to > 1000 pg L" hr t. An alteration in microbial composition was noted over this period, from a denitrifying `co-metabolic' culture to predomination of `high-rate' specific bromate degraders. Operational parameters including pH, temperature, carbon source, influent bromate and glucose, and retention times were investigated, with all parameters apart from pH shown to affect bromate reduction rates. For example increased bromate influent enhanced reduction rate, although potentially toxic effects were noted with an influent > 75 - 80 mg L"'. Batch studies suggested glucose was rapidly fermented (< 48 hours) by the microbial consortium. Nitrate was also rapidly removed (< 4 hours), with sulphate reduction only following removal of bromate. A fixed- film pilot-scale bioreactor system, seeded with biomass from the chemostat culture, reduced > 90% of a 1.1 mg L"1 bromate influent within unspiked contaminated groundwater. Plating studies were successful in producing a range of isolates from the mixed chemostat culture. Overall the project demonstrated, for the first time, continuous remediation of bromate groundwater contamination within a bioreactor system.